Selective Transmission of Phonons in Molecular Junctions with Nanoscopic Thermal Baths - Sandonas, Leonardo Medrano; Mendez, Alvaro Rodriguez; Gutierrez, Rafael; Ugalde, Jesus M.; Mujica, Vladimir; Cuniberti, Gianaurelio (Giovanni) (Journal of Physical Chemistry C, 2019)
A fundamental problem for thermal energy harvesting is the development of atomistic design strategies for smart nanodevices and nanomaterials that can be used to selectively transmit heat. We carry out here an extensive computational study demonstrating that heterogeneous molecular junctions, consisting of molecular wires bridging two different nanocontacts, can act as a selective phonon filter. The most important finding is the appearance of gaps on the phonon transmittance spectrum, which are strongly correlated to the properties of the vibrational spectrum of the specific molecular species in the junction. The filtering effect results from a delicate interplay between the intrinsic vibrational structure of the molecular chains and the different Debye cutoffs of the nanoscopic electrodes used as thermal baths.
CRIS-Team Scopus Importer:2022-04-14